Cellular automata and discrete complex systems : 25th IFIP WG 1.5 International Workshop, AUTOMATA 2019, Guadalajara, Mexico, June 26-28, 2019, Proceedings /: 25th IFIP WG 1.5 International Workshop, AUTOMATA 2019, Guadalajara, Mexico, June 26-28, 2019, Proceedings. (2019) - Unknown
No abstract available